Presenting treatment options in breast cancer consultations: Advice and consent in Italian medical care. (December 2020) - Fatigante, Marilena; Heritage, John; Alby, Francesca; Zucchermaglio, Cristina
Abstract: Variety, complexity and uncertainty in the therapy outcomes of cancer illness make the treatment recommendation (TR) in oncology a "monumentally difficult task". Previous studies have distinguished unilateral and bilateral formats of treatment recommendations, accordingly to whether, or to what extent, the patient's perspective is included in the consideration of therapeutic options. Others have also shown how the oncologists' presentation of therapeutic options varied accordingly to the severity of the diagnosis and the availability of alternatives. Yet, no study has systemically dentified and compared components of treatment recommendation in oncology on a common set of patients and clinicians. This paper analyzes how different options in breast cancer treatments - radiotherapy, hormone therapy and chemotherapy - are presented and discussed in a set of 12 first post-surgical breast cancer visits carried out by two oncologists of high experience and seniority in two Italian hospitals. Treatment recommendation sequences involving these three option types were analyzed using the methods of conversation analysis. They were also coded for the mention of side effects and treatment burden, and for whether consent to the recommendation was invited, or expressed by the patient. Results show that radiotherapy is presented as presupposed as an extension of surgery and is not further discussed, and hormone therapy is delivered as good news and as not implying any health or lifestyle burdens. Treatment burdens were raised in the much more extensive discussions of chemotherapy, which were also accompanied by a higher chance that the patient was asked for consent to therapy. Implications are drawn as regards the extent to which clinical practice meets theory in communication protocols available in oncology, and how to consider the doctor-patient partnership and the concept of shared decision-making in such an encounter. Highlights: Oncologists deliver recommendation for different cancer treatments in different ways. Radiotherapy is presented as presupposed, hormonetherapy is delivered as good news. Oncologists anticipate the patient's burden only in chemotherapy. There is a gap between protocols and communication practices in oncology. Consent -gaining process needs be followed across time and settings.